Developing a Digital Learning Management Strategy Using the Dick and Carey Model to Enhance Junior High School Students' Critical Thinking in Biology Learning - Sasongko, Enggar Jati; Djono; Solihah, Khoirur Rohmaniatush; Putri, Marchecal Carissima Haipa; Muiz, Abdul (Universitas Sebelas Maret, 2025)
Biology learning at the junior secondary school level faces increasing challenges in fostering students' critical thinking skills as a core competency of the 21st century. International assessments consistently indicate that students' higher-order thinking skills in science remain relatively low, highlighting the need for learning strategies that emphasize systematic learning management rather than content transmission alone. This study aims to develop and examine the effectiveness of a digital learning management strategy through the integration of the Nearpod web-based platform using the Dick and Carey instructional design model to enhance junior high school students' critical thinking skills in biology. This research employed a Research and Development (R&D) approach following the nine stages of the Dick and Carey model, including needs analysis, instructional analysis, learner analysis, instructional design, formative evaluation, revision, and field implementation. The participants consisted of 72 eighth-grade students, three biology teachers, two media experts, and one educational technology expert. Data were collected through observations, questionnaires, critical thinking tests, interviews, and Nearpod learning analytics and analyzed using qualitative techniques and gain score analysis. The results indicate an average increase of 26.8% in students' critical thinking skills (N-Gain 0.44), categorized as medium-high, demonstrating that systematically managed digital learning effectively supports higher-order cognitive processes. The study concludes that integrating Nearpod as a digital instructional management system within a coherent instructional design framework significantly enhances biology learning quality. This research contributes theoretically by linking instructional design, digital learning management, and critical thinking development, and practically by offering an implementable model for technology-enhanced science instruction.